Effects of phytase-supplemented fermentation and household processing on the nutritional quality of Lathyrus sativus L. seeds. Issue 11 (November 2020) - Buta, Meseret Bekele; Posten, Clemens; Emire, Shimelis Admassu; Meinhardt, Ann-Katrin; Müller, Alexandra; Greiner, Ralf
Abstract: Grass pea ( Lathyrus sativus L.) is commonly consumed in cooked, fermented, and roasted forms in Ethiopia. However, the impacts of household processing practices on its nutrients, antinutrients, and toxic compounds have not been adequately studied. Therefore, the effects of household processing and fermentation in the presence and absence of a phytase on the contents of β-N-oxalyl-L-α, β-diaminopropionic acid (β-ODAP), myo -inositol phosphates, crude protein, minerals and the in vitro bioaccessibility were investigated. Fermentation exhibited a significant decline in β-ODAP (13.0–62.0%) and phytate (7.3–90.5%) irrespective of the presence of phytase. Pressure and pan cooking after discarding the soaking water resulted in a 27.0 and 16.2% reduction in β-ODAP. A 30% reduction in phytate was observed during germination followed by roasting. In addition, germination resulted in a significant (p < 0.05) increase in crude protein. Germination and germination followed by roasting resulted in the highest Fe bioaccessibilities (more than 25 fold higher compared to untreated samples) followed by pressure cooking and soaking. Processing also improved Zn bioaccessibilities by 50.0% (soaked seed without soaking water), 22.5% (soaked seed with soaking water), and 4.3% (germination). Thus, the processing technologies applied were capable of reducing the content of phytate (InsP6 ) and β-ODAP with a concomitant increase in mineral bioaccessibilities. Processing of grass peas could therefore contribute to their more widespread utilization. Abstract : Food science; Food analysis; Grass pea; Household processing; β-ODAP; Myo -inositol phosphates; Mineral bioaccessibility; Phytase